PERANCANGAN HOTEL DENGAN PENDEKATAN ARSITEKTUR KONTEMPORER DI MANADO - Dududuk, Yusak; D.J. Mailangkay, Sonny; Budhyowati, M. Y. Noorwahyu (Program Studi Arsitektur Fakultas Teknik Universitas Negeri Manado, 2024)
ABSTRACT A hotel is an accommodation service business which includes elements of service, comfort and security, which is intended for those who need accommodation facilities for family purposes, business meetings, entertainment and other activities. The city of Manado is located on the northern island of Sulawesi, and is also the capital of North Sulawesi Province. Based on data from the North Sulawesi Central Statistics Agency (BPS) in 2019, the number of foreign tourist visits increased 3.72% compared to the previous year, and the cumulative number of incoming foreign tourists in 2019 reached 132,999 people. This figure increased by 6.54% compared to the number of foreign tourists entering in the previous year. Developments in the tourism sector encourage the growth of the hotel business in Manado to accommodate the number of tourists who continue to arrive. In this design, I will apply the Contemporary Architecture theme which is always evolving following the development of modernization in terms of structure, aesthetics, utility and function as well as paying attention to the surrounding natural conditions. This Engineering Thesis with the title Hotel Design with a Contemporary Architectural Approach in Manado will later support the needs of tourists visiting Manado with complete facilities that are of 5 Star Hotel standard and can apply contemporary themes that are always evolving following existing modernization developments in terms of structure, aesthetics, utility, and function while remaining in harmony with the surrounding natural conditions.